2015
DOI: 10.1016/j.neubiorev.2014.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Diet, behavior and immunity across the lifespan

Abstract: It is increasingly appreciated that perinatal events can set an organism on a life-long trajectory for either health or disease, resilience or risk. One early life variable that has proven critical for optimal development is the nutritional environment in which the organism develops. Extensive research has documented the effects of both undernutrition and overnutrition, with strong links evident for an increased risk for obesity and metabolic disorders, as well as adverse mental health outcomes. Recent work ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 306 publications
(398 reference statements)
0
14
0
Order By: Relevance
“…Tame and aggressive foxes are maintained under the same farm conditions; thus, it is more likely that differences in genomic regions containing immune genes are directly or indirectly associated with selection for behavior. The link between behavior and immunity has been demonstrated in a large body of literature (reviewed in References ).…”
Section: Discussionmentioning
confidence: 99%
“…Tame and aggressive foxes are maintained under the same farm conditions; thus, it is more likely that differences in genomic regions containing immune genes are directly or indirectly associated with selection for behavior. The link between behavior and immunity has been demonstrated in a large body of literature (reviewed in References ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, maternal overnutrition and/or obesity during pregnancy can have long-term effects on metabolic and cardiovascular traits in adult offspring [ 1 , 4 ]. Maternal consumption of a high-fat diet and/or obesity also affect offspring mental health in humans as well as behaviour in animal models [ 2 , 3 , 6 , 7 ], including voluntary locomotor activity [ 8 , 9 ]. Similarly, early postnatal nutrition influences voluntary physical activity in adulthood [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms to explain how maternal obesity can induce an increased likelihood of offspring obesity is altered prenatal development of the hypothalamus (Hale et al, 2014;Sanders et al, 2016). Studies have shown that the neuroendocrine networks that regulate energy homeostasis develop differently when a fetus develops in an obese maternal environment (Sanders et al, 2016;Chang et al, 2008;Gupta et al, 2009;Grayson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%